2023
DOI: 10.7150/jca.81795
|View full text |Cite
|
Sign up to set email alerts
|

Venetoclax Penetrates the Blood Brain Barrier: A Pharmacokinetic Analysis in Pediatric Leukemia Patients

Abstract: Infiltration of malignant cells into the central nervous system in hematological malignancies correlates with poor clinical outcomes. Investigations into the penetration of venetoclax into the central nervous system have been limited. We report venetoclax pharmacokinetics in plasma and cerebrospinal fluid samples from a Phase 1 study in pediatric patients with relapsed or refractory malignancies that demonstrate venetoclax ability to cross into the central nervous system. Venetoclax was detected in cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In addition, Badawi et al reported the pharmacokinetics of VEN in plasma and CSF samples from pediatric patients with R/R malignancies from a Phase 1 study, which demonstrates VEN's ability to cross into the central nervous system. 31 In light of these findings, VEN may have a role to play for patients with CNS complications. However, there is a need for further research in order to determine its utility in improving clinical outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Badawi et al reported the pharmacokinetics of VEN in plasma and CSF samples from pediatric patients with R/R malignancies from a Phase 1 study, which demonstrates VEN's ability to cross into the central nervous system. 31 In light of these findings, VEN may have a role to play for patients with CNS complications. However, there is a need for further research in order to determine its utility in improving clinical outcomes.…”
Section: Discussionmentioning
confidence: 98%
“… 17 The mean plasma‐to‐CSF ratio was 385 with a range of 44–1559, the mean is more than fourfold higher than the blood‐to‐brain ratio observed preclinically in mice, which suggests that other anatomical and/or physiological factors are involved in venetoclax disposition to the CSF. 17 …”
Section: Physicochemical Properties and Admementioning
confidence: 95%
“…Venetoclax can cross the blood–brain barrier as demonstrated in an open‐label, phase I study in 46 pediatric patients with relapsed/refractory (R/R) AML, acute lymphoblastic leukemia (ALL), or other hematological malignancies. Venetoclax concentrations in cerebrospinal fluid (CSF) were between <0.1 and 26 ng/mL with a mean concentration of 3.6 ng/mL 17 . The mean plasma‐to‐CSF ratio was 385 with a range of 44–1559, the mean is more than fourfold higher than the blood‐to‐brain ratio observed preclinically in mice, which suggests that other anatomical and/or physiological factors are involved in venetoclax disposition to the CSF 17 …”
Section: Physicochemical Properties and Admementioning
confidence: 99%
See 1 more Smart Citation